Adaptations on jump capacity in Brazilian volleyball players prior to the under-19 World Championship - Stanganelli, L. C. R.; Dourado, A. C.; Oncken, P.; Mancan, S.; da Costa, S. C. (The Journal of Strength and Conditioning Research, 2008)
The under-19 Brazilian volleyball national team has achieved great performances at international competitions. Because the vertical jump capacity is critical for success in volleyball, the purpose of this study was to identify the training-induced adaptations on jump capacity assessed by general and specific tests during 3 different moments (i.e., T1, T2, and T3) of a macrocycle of preparation for the world championship. The sample was composed of 11 athletes from the Brazilian national team-World Champion (age, 18.0 ± 0.5 years; height: 198.7 ± 5.4 cm; and body mass, 87.3 ± 5.9 kg). They were evaluated for jumping capacity by the following tests: squat jump (SJ), countermovement jump (CMJ), and jump anaerobic resistance (15 seconds) (JAR) and standing reach, height, and vertical jump tests for attack and block. Descriptive statistics were computed, and a repeated-measures analysis of variance was used. The Tukey-Kramer post hoc test was used when appropriate. Significance was set at P <= 0.05. The results showed that the training-induced adaptations on the SJ (3.9%) and CMJ (2.3%) were not statistically significant. The JAR showed statistical significance between T2 and T3 (9.6%), while the attack height and block height presented significant differences between T1 and T2 (2.5% and 3.3%, respectively) and T1 and T3 (3.0% and 3.5%, respectively). The volume of training was quantified between weeks 1 and 9 (10,750 minutes, 1,194 ± 322 min·wk-1) and between weeks 10 and 18 (8,722 minutes, 969 ± 329 min·wk-1). In conclusion, this study showed that there were progressive and significant training-induced adaptations, mainly on the tests that simulated the specific skills, such as spike and block, with the best results being reached after the first 9 weeks of training. This probably reflected not only the individual's capacity to adapt, but also the characteristics of the training loads prescribed during the entire macrocycle.